2020
DOI: 10.1136/bcr-2019-233144
|View full text |Cite
|
Sign up to set email alerts
|

Wernicke’s encephalopathy-induced hearing loss complicating sleeve gastrectomy

Abstract: A 25-year-old woman brought to the hospital with symptoms of acute confusion, disorientation, diplopia, hearing loss and unsteady gait which started 4 days prior to her presentation with rapid worsening in its course until the day of admission. She had a surgical history of laparoscopic sleeve gastrectomy 2 months earlier which was complicated by persistent vomiting around one to three times per day. She lost 30 kg of her weight over 2 months and was not compliant to vitamin supplementation. CT of the brain wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The pathogenesis of hearing loss in patients with WE is not clear. It is assumed to be due to the impairment of geniculate nuclei of thalamus and peripheral damage to acoustic nerves because of thiamine de ciency [4].Cases of WE presenting with bilateral blindness and bilateral deafness are fairly rare.…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…The pathogenesis of hearing loss in patients with WE is not clear. It is assumed to be due to the impairment of geniculate nuclei of thalamus and peripheral damage to acoustic nerves because of thiamine de ciency [4].Cases of WE presenting with bilateral blindness and bilateral deafness are fairly rare.…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…The pathogenesis of hearing loss in patients with WE is not clear. It is assumed to be due to the impairment of geniculate nuclei of the thalamus and peripheral damage to the acoustic nerves because of thiamine deficiency [ 7 ].Cases of WE presenting with bilateral blindness and bilateral deafness are fairly rare. Moussa et al [ 3 ] reported a case of a chronically vomiting man with bilateral blindness that was associated with bilateral perceptual hypoacousia, revealing the presence of WE.…”
Section: Discussionmentioning
confidence: 99%
“…[ 53 , 54 ] Besides the usual presentations, WE can sometimes present with atypical symptoms such as hypothermia, papilloedema, seizures, and hearing loss. [ 6 , 55 ] Most of the hearing loss improves after thiamine therapy;[ 6 ] one case report noted a minimal persistent sensorineural hearing impairment. [ 55 ]…”
Section: Thiamine Deficiency After Gastrectomymentioning
confidence: 99%
“…[ 6 , 55 ] Most of the hearing loss improves after thiamine therapy;[ 6 ] one case report noted a minimal persistent sensorineural hearing impairment. [ 55 ]…”
Section: Thiamine Deficiency After Gastrectomymentioning
confidence: 99%